2001
DOI: 10.1097/00000542-200105000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine Increases the Neurotoxic Potential of Intrathecally Administered Lidocaine in the Rat

Abstract: The neurotoxicity of intrathecally administered lidocaine is increased by the addition of epinephrine. When making clinical recommendations for maximum safe intrathecal dose of this anesthetic, one may need to consider whether the solution contains epinephrine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 1 publication
0
31
0
3
Order By: Relevance
“…We should keep in mind that when these patients are in the supine position and epinephrine is added to intrathecal local anaesthetics, we have a higher possibility to expose the patients to a high level of spinal blockade. The neurotoxic potential of intrathecal epinephrine (13) has also to be taken into consideration when the spinal anaesthetic plan is made.…”
Section: Discussionmentioning
confidence: 99%
“…We should keep in mind that when these patients are in the supine position and epinephrine is added to intrathecal local anaesthetics, we have a higher possibility to expose the patients to a high level of spinal blockade. The neurotoxic potential of intrathecal epinephrine (13) has also to be taken into consideration when the spinal anaesthetic plan is made.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that a single intrathecal injection of plain epinephrine (up to 0.5 mg) is not associated with histological injury in rabbits (Oka et al, 2001) or rats (Bahar et al, 1984;Hashimoto et al, 2001). However, epinephrine worsens histological spinal cord injury when added to 5% lidocaine in rats (Hashimoto et al, 2001) or 1-2% tetracaine in rabbits (Oka et al, 2001).…”
Section: Local Toxicity Evaluationmentioning
confidence: 99%
“…However, epinephrine worsens histological spinal cord injury when added to 5% lidocaine in rats (Hashimoto et al, 2001) or 1-2% tetracaine in rabbits (Oka et al, 2001). Thus, it seems that the addition of epinephrine to a potential irritating substance (local anesthetic) worsens the tissue reaction.…”
Section: Local Toxicity Evaluationmentioning
confidence: 99%
“…41 Ischemia is one of the possible causative mechanisms that may result from changes in peripheral blood flow. 42 An immune-mediated mechanism may be possible as suggested by others. 21,43 In the current study, we observed that the local inflammatory process associated with the Rop-PELA might be due to the stimuli by unabsorbed Rop nanoparticles.…”
mentioning
confidence: 93%